(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the intricate structure of dictionaries, examining their essential components and the principles that govern their organization. It begins by defining the fundamental types of dictionaries monolingual, bilingual, specialized, and historical highlighting their unique purposes and audiences. The discussion then delves into the core elements of dictionary entries, including headwords, definitions, phonetic transcriptions, usage examples, and grammatical information. Attention is given to the methodologies employed in selecting and arranging entries, with a focus on alphabetical order, thematic categorization, and frequency-based listings. The article also addresses the role of technology in modern dictionary-making, including digital formats and online databases, which have transformed accessibility and user interaction. Furthermore, the annotation emphasizes the importance of lexicographic principles such as accuracy, comprehensiveness, and user-friendliness in creating effective reference tools. By analyzing various dictionary structures, the article aims to provide insights into how these resources reflect linguistic diversity and evolve with language use. This exploration contributes to a deeper understanding of lexicography as both a science and an art, ultimately enhancing the appreciation of dictionaries as vital tools for communication and learning